Analisis Dan Perancangan Sistem Publikasi Realisasi Anggaran Desa - I Gusti Ayu Aris Dwiyanti; I Gede Juliana Eka Putra; I Nyoman Purnama (STMIK Banjarbaru, 2021)
Information services for the implementation of the Village Fund Allocation from the village government to the community are still manual so that the information received by the community is still minimal. This article aims to analyze and design an information system model for the publication of village budget realization, so that the community can easily access information anywhere and anytime regarding the realization of the village budget in Keramas Gianyar Village. This study uses the software development life cycle (SDLC) method with a linear sequential model, where the tools used in designing the village budget realization publication system use Data Flow Diagrams (DFD), Databases using Entity Relational Database (ERD), Data Dictionary. The results of the System Usability Scale (SUS) test show that the average score is at a value of 77, indicating that the user interface of the village budget realization publication system in Keramas Village is at grade B with an Adjective Rating Good.Keywords: Accounting Information System, Village Fund Allocation, Village Publication System ABSTRAK. Layanan informasi pelaksanaan Alokasi Dana Desa dari pemerintah desa ke masyarakat masih manual sehingga informasi yang diterima masyarakat masih minim. Artikel ini bertujuan untuk menganalisis dan merancang model sistem informasi untuk publikasi realisasi anggaran desa, agar masyarakat dapat dengan mudah mengakses informasi dimana saja dan kapan saja mengenai realisasi anggaran desa di Desa Keramas Gianyar. Penelitian ini menggunakan metode software development life Cycle (SDLC) dengan model sekuensial linier, dimana tools yang digunakan dalam merancang sistem publikasi realisasi anggaran desa menggunakan Tools Data Flow Diagram (DFD), Basis Data yang menggunakan Entity Relational Database (ERD), Kamus Data. Hasil pengujian System Usability Scale (SUS) menunjukkan Skor rata-rata berada pada nilai 77, menunjukkan user interface sistem publikasi realisasi anggaran desa di Desa Keramas berada pada grade B dengan Adjective Rating Good.Kata kunci: Sistem Informasi Akuntansi, Alokasi Dana Desa, Sistem Publikasi Desa